The usefulness of diffusion tensor imaging in detection of diffuse axonal injury in a patient with head trauma - Kwon, Hyeok Gyu (Neural Regen Res, 2012)
Diffuse axonal injury is the predominant mechanism of injuries in patients with traumatic brain injury. Neither conventional brain computed tomography nor magnetic resonance imaging has shown sufficient sensitivity in the diagnosis of diffuse axonal injury. In the current study, we attempted to demonstrate the usefulness of diffusion tensor imaging in the detection of lesion sites of diffuse axonal injury in a patient with head trauma who had been misdiagnosed as having a stroke. A 44-year-old man fell from a height of about 2 m. Brain magnetic resonance imaging (32 months after onset) showed leukomalactic lesions in the isthmus of the corpus callosum and the left temporal lobe. He presented with mild quadriparesis, intentional tremor of both hands, and trunkal ataxia. From diffusion tensor imaging results of 33 months after traumatic brain injury onset, we found diffuse axonal injury in the right corticospinal tract (centrum semiovale, pons), both fornices (columns and crus), and both inferior cerebellar peduncles (cerebellar portions). We think that diffusion tensor imaging could be a useful tool in the detection of lesion sites of diffuse axonal injury in patients with head trauma.